2016
DOI: 10.1021/acs.analchem.6b03534
|View full text |Cite
|
Sign up to set email alerts
|

FAST: Size-Selective, Clog-Free Isolation of Rare Cancer Cells from Whole Blood at a Liquid–Liquid Interface

Abstract: Circulating tumor cells (CTCs) have great potential to provide minimally invasive ways for the early detection of cancer metastasis and for the response monitoring of various cancer treatments. Despite the clinical importance and progress of CTC-based cancer diagnostics, most of the current methods of enriching CTCs are difficult to implement in general hospital settings due to complex and time-consuming protocols. Among existing technologies, size-based isolation methods provide antibody-independent, relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
120
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 35 publications
0
120
0
Order By: Relevance
“…However, the non-uniform and randomly distributed pores and low porosity of these membranes can cause inconsistent and lower-than-desired recoveries and purity [28, 29]. Here, we used a centrifugal microfluidic device operated in FAST mode to overcome the limitations of track-etched based filtration using a hydrodynamic approach [10]. FAST provides uniform, clog-free, and efficient filtration under a lower pressure drop when compared to conventional separation, leading to highly sensitive (>95.9% recovery), selective (~2.5 log depletion of white blood cells), rapid (>3 mL/min), and label-free isolation of CTCs from whole blood without prior sample treatment [10, 11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the non-uniform and randomly distributed pores and low porosity of these membranes can cause inconsistent and lower-than-desired recoveries and purity [28, 29]. Here, we used a centrifugal microfluidic device operated in FAST mode to overcome the limitations of track-etched based filtration using a hydrodynamic approach [10]. FAST provides uniform, clog-free, and efficient filtration under a lower pressure drop when compared to conventional separation, leading to highly sensitive (>95.9% recovery), selective (~2.5 log depletion of white blood cells), rapid (>3 mL/min), and label-free isolation of CTCs from whole blood without prior sample treatment [10, 11].…”
Section: Discussionmentioning
confidence: 99%
“…The “FAST disc” centrifugal microfluidic system, which conducts size-selective CTC isolation through membrane pores filled with a stably held liquid throughout the filtration process, was used to detect CTCs [10, 11]. FAST disc isolation of CTCs allows the use of whole blood without any sample treatment steps (e.g., dilution and red blood cell lysis).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although immunohistochemistry, reverse transcriptase polymerase chain reaction (PCR), flow cytometry, and the CellSearch system are currently used in clinical research, each technology has its own methodological limitations and uncertainty and may lead to different results. To directly identify CTCs in the blood, we recently developed a centrifugal microfluidic system based on a new fluid‐assisted separation technique (FAST), in which size‐based separation occurs within a centrifugal microfluidic device at a liquid–liquid interface, instead of the conventional liquid–gas interface . In a previous study, we showed that FAST enabled a highly sensitive, selective, rapid, and label‐free isolation of CTCs from whole blood directly without prior sample manipulation .…”
Section: Introductionmentioning
confidence: 99%